Discovered: Joseph Étienne de Surville's Preface to the Poésies de Clotilde de Surville. (18th December 2020) - Cole, William
Abstract: Joseph Étienne, marquis de Surville (1755–1798) composed a wildly successful book of poems, first published in 1803, that he passed off as the work of his ancestor Clotilde de Surville ( c . 1405- c . 1498). A newly-discovered copy of the first edition—presented by the author's widow to a family friend—contains Joseph Étienne's preface, transcribed and published here for the first time.